2008
DOI: 10.37236/778
|View full text |Cite
|
Sign up to set email alerts
|

A New Family of Somos-like Recurrences

Abstract: We exhibit a three parameter infinite family of quadratic recurrence relations inspired by the well known Somos sequences. For one infinite subfamily we prove that the recurrence generates an infinite sequence of integers by showing that the same sequence is generated by a linear recurrence (with suitable initial conditions). We also give conjectured relations among the three parameters so that the quadratic recurrences generate sequences of integers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 3 publications
3
26
0
1
Order By: Relevance
“…This agrees with the result of [14, Theorem 5.1], and with the particular integer sequence considered in [12]: putting the initial data x 0 = x 1 = x 2 = 1 with a = 1 into (3.16) gives the constant value K = 14, in accordance with Proposition 1.1 for k = 1.…”
Section: Linearizabilitysupporting
confidence: 91%
See 1 more Smart Citation
“…This agrees with the result of [14, Theorem 5.1], and with the particular integer sequence considered in [12]: putting the initial data x 0 = x 1 = x 2 = 1 with a = 1 into (3.16) gives the constant value K = 14, in accordance with Proposition 1.1 for k = 1.…”
Section: Linearizabilitysupporting
confidence: 91%
“…However, observe that the right-hand side of (1.4) has N terms, which means that for N 3 it cannot be obtained from an exchange relation in a cluster algebra, since for that to be so the polynomial F should have the same binomial form as (1.3); the case N = 2 is not an exchange relation either (but see [8,Example 4.11]). The inspiration for (1.4) comes from results of Heideman and Hogan [12], who considered odd order recurrences of the form 5) and showed that an integer sequence is generated for initial data…”
Section: Introductionmentioning
confidence: 99%
“…Notice that it just depends upon the ℓ th column of the matrix. Since the matrix is skew-symmetric, the variable x ℓ does not occur on the right side of (17). After this process we have a new quiverQ, with a new matrixB.…”
Section: Recurrences With the Laurent Propertymentioning
confidence: 99%
“…which can be interpreted as a two-dimensional extension of (1). Another interesting linearizable mapping we mainly study in this paper is the Heideman-Hogan recurrence [14]:…”
Section: Introductionmentioning
confidence: 99%